2021
DOI: 10.1007/s11469-020-00466-y
|View full text |Cite
|
Sign up to set email alerts
|

Positive Psychology for Mental Wellbeing of UK Therapeutic Students: Relationships with Engagement, Motivation, Resilience and Self-Compassion

Abstract: This study aimed to examine the relationships between mental wellbeing and positive psychological constructs in therapeutic students (psychotherapy and occupational therapy students). The number of therapeutic students has increased recently; however, they suffer from poor mental health, which may be improved by potentiating their positive psychological constructs, bypassing mental health shame. Therapeutic students (n = 145) completed measures regarding positive psychological constructs, namely mental wellbei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 88 publications
1
17
0
Order By: Relevance
“…This, coupled with our qualitive findings from the same sample, demonstrates a clear need to support and promote wellbeing in healthcare trainees. The package explored in this study provides a wealth of support and advice to facilitate engagement and motivation, build resilience and foster self-compassion-all factors that have been associated with mental wellbeing in students from the caring professions [68].…”
Section: Discussionmentioning
confidence: 99%
“…This, coupled with our qualitive findings from the same sample, demonstrates a clear need to support and promote wellbeing in healthcare trainees. The package explored in this study provides a wealth of support and advice to facilitate engagement and motivation, build resilience and foster self-compassion-all factors that have been associated with mental wellbeing in students from the caring professions [68].…”
Section: Discussionmentioning
confidence: 99%
“…Developing grit and resilience as an aspect of perseverance has effects on academic and individual success (Stoffel et al, 2018). Many studies found that resilience is a key concept of students' well-being and it is related to their engagement and motivation as well (Kotera et al, 2021;Datu, 2018). Resilience can be enhanced even in the university context and is related to motivation and growing experiences (Bryan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Positive psychology could be an umbrella in each faculty, in the case of management and economics students in the subjective and personal level, and institutional level as well (Seligman et al, 2005;Field et al, 2015). On the other hand, according to literature (for example Kotera et al 2021;Kashdan, Ciarrochi, 2013;Forsman et al, 2015;Martin, 2009;Chodkiewitz, Boyle, 2016;Horn et al 2011) positive psychological interventions seem to be not so direct as therapeutic interventions and in this way students feel more comfortable to use them for strengthening their life skills and values. Positive psychological approach-based interventions are important by facing challenges of the everyday life in the personnel, university, and work context for a better quality of life (Vella-Broderick, 2011;Ng, 2015;Chodkiewitz, Boyle, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is theorized that the theories and studies of positive psychology related to the organizational context are acknowledged as PsyCap's tools (Cetin & Basim, 2012). Successful organizational action that corporate positive psychology into the organizational field is a modern approach that aims at people's growth by highlighting their strengths rather than their weakness (Kotera, Green & Sheffield, 2021). Studies have shown that PsyCap, with its connection to organizational efficiency, can leverage the organizational performance of all sizes, including the public and private sector institutions (Silveira-Rodrigues, Chambel & Carvalho, 2021).…”
Section: Introductionmentioning
confidence: 99%